The Requirement of Applying the Change Leadership in Kindergarten organizations in Damascus City (Damascus University Journal of educational and Psychologyical sciences, 2021)
This research aims at identifying the requirements of applying change leadership in kindergarten  organizations in Damascus City and knowing the differences between the mean scores of the sample on the scale related to the variables of dependence, scientific qualification and years of service .To achieve this aim, the research used the descriptive analytical approach and applied the scale on a random sample (300) female kindergarten in Damascus City in the first semester of the academic year 2018-2019. The research results indicated that the requirements were identified in terms of four dimension which are management, female teachers and children, curriculum, financial technical and technological resources, and the relationship with the local society. In addition, the results indicated that the need for them was high and there were statistically significant differences at the level (0.05) between the men scores of kindergarten principals according the dependence variable on the total degree in favour of state kindergartens. The results also indicated that there were no statistically significant differences at the level (0.05) between the men scores of female principals according the scientific qualification. The results also indicated that there were no statistically significant differences at the level (0.05) between the mean score of females principals on the total score of the scale related to the variable of year of experience in terms of the men scores of the female principals of years of experience less than (5) years and (5-10). It was revealed that there were statistically significant differences between the mean scores of the principals with years of service (less5) and those with more than (10 years) in favour of female principals who have more than ten years of service.
Keywords: The Requirement of Applying the Change Leadership in Kindergarten organizations in Damascus City